The influence of nutrient media modification on the morphological parameters in raspberry (Rubus idaeus L.) micropropagation in the liquid and semi-solid media - Bošnjak, Dejan (Array, 2021)
Within the nursery sector, a global interest in functional fruits imposes a permanent need to improve the tissue culture technology. A modern bioreactor immersion system is currently a valid solution for the micropropagation of many cultures. At the Faculty of Agrobiotechnical Sciences Osijek (FAZOS, Croatia), a research was conducted with the aim of improving the raspberry (Rubus idaeus L., cv. HimboTop®) micropropagation protocol. The treatments implied the modifications of the MS and DKW nutrient medium (DKW – standard; DKWm – substitution of FeEDTA with the FeEDDHA; MSm – macroelement modification, 3 x CaCl2, MgSO4, and KH2PO4 + FeEDDHA), differently depending on the aggregate condition (semi‐solid and liquid SETISTM). Subsequent to 15 (SETISTM) and 30 cultivation days (semi-solid medium), respectively, a morphological parameter analysis and a multiplication success evaluation were commenced. In all treatments (DKW, DKWm, and MSm), the observed parameters (shoot height, number of leaves, leaf width and length) were significantly better in an interaction with the liquid medium. Comparing the models, a liquid medium (SETISTM) resulted in a significantly higher explant multiplication (4.02) (a semi‐solid medium - 2.74). The best reproduction quality, implying a better plant vigor with a reduced vitrification, was obtained on the MSm medium in the SETISTM. A concentration optimization of individual mesocomponents (i.e., of the macroelements) and their chemical forms (FeEDDHA) may contribute to their improved adoption and consequently to the stress suppression due to an explant transplantation. Selecting the modern technical solutions (TIS bioreactors - SETISTM) and continuously improving the protocols, we may obtain the realistically sustainable models, suitable for a massive clonal reproduction.